A gentle madness : bibliophiles, bibliomanes, and the eternal passion for books : with a new preface - Basbanes, Nicholas A., 1943- (New York : H. Holt, 1952)
A history of book lore, book culture, and book lovers begins in Alexandria more than 2,500 years ago and passes through the Middle Ages and the Renaissance to the present, offering special emphasis on collecting in Great Britain and North America.
Touching the hand -- Balm for the soul -- Rule Britannia -- America, Americans, Americana -- Brandy for heroes -- To have and to have no more -- Infinite riches -- Mirror images -- Instant ivy -- Obsessed amateurs -- Destiny -- Continental drift -- The Blumberg collection -- Carpe Diem.
"An Owl book."
Includes bibliographical references (p. 575-612) and index.
Keywords: Book collecting; Bibliomania